ANTHROPOMETRY ASSESSMENT OF NUTRITIONAL STATUS OF TRIBAL ADOLESCENT GIRLS OF KEONJHAR DISTRICT, ODISHA - VIJAYETA PRIYADARSHINI* (The Journal of Research ANGRAU, 2023)
This study was conducted in year 2021 -2022 in Keonjhar district of Odisha, in which 45% of the population belongs to tribal community. The study was conducted in five tribal dominated blocks of Keonjhar (Banspal, Keonjhar, Harichandanpur, Joda, Ghatgaon) among 301 adolescent girls aged between 16 and 18 years. The study revealed that the average height of the tribal adolescent girls was 149.82±2.265 cm, body weight was 39.126±0.022 kg and BMI was 17.43351±1.059 kg m-2. The mean weight, height was found to be less than that of 50th percentile of NCHS standards in every age group. Only 20.6% of tribal adolescent girls were found to be within the normal range of BMI value (18.5-22.9 kg m-2) and the rest 79.4% were underweight (< 18.5 kg m-2 ) category. The research revealed that there was a statistically significant association between number of family members, family income and socio-economic status with BMI. However, no significant association was found in between age and educational qualification of the respondents with BMI value